Endowment life insurance - Zeljko Sain; Jasmina Selimovic (UTMS Journal of Economics, 2013)
The aim of the paper that treats the actuarial model of insurance in case of survival or early death is to show the actuarial methods and methodology for creating a model and an appropriate number of sub-models of the most popular form of life insurance in the world. The paper applies the scientific methodology of the deductive character based on scientific, theoretical knowledge and practical realities. Following the basic theoretical model's determinants, which are at the beginning of the paper, the basic difference between models further in this paper was carried out according to the character of the premium to be paid. Finally, the financial repercussions of some models are presented at examples in insurance companies. The result of this paper is to show the spectrum of possible forms of capital endowment insurance which can be, without major problems, depending on the financial policy of the company, applied in actual practice. The conclusion of this paper shows the theoretical and the practical reality of this model, life insurance, and its quantitative and qualitative guidelines.
Keywords: G22; 330; capital endowment insurance; life insurance; actuarial mathematics of life insurance; the insured; the insurer; the risk in life insurance